352 PHOTODYNAMIC THERAPY COMBINING INTENSE PULSED LIGHT AND TOPICAL 5-AMINOLEVULINIC ACID FOR THE TREATMENT OF ROSACEA-ASSOCIATED ERYTHEMA. Issue 1 (1st January 2007) - Davis, M.; Shores, J.; Gabriel, A.; Gupta, S.
Abstract : Background: Rosacea is a chronic cutaneous disease that primarily affects the facial convexities and is characterized by signs and symptoms such as flushing, persistent erythema, and telangiectasias. Although there are many methods of treating rosacea ranging from topical and oral agents to a variety of light-based therapies, there is no cure. Here we report our experience with a novel method of treatment. We used photodynamic therapy with topical 5-aminolevulinic acid (ALA) as a sensitizer and intense pulsed light (IPL) activation. Methods: Four female patients with rosacea were included in this study. All patients were started on a hydroquinone and retinol-based skin priming system at least 8 weeks prior to treatment to produce preprocedure sensitization. After incubation with ALA for 45 minutes to 1 hour, patients were treated with IPL at a fluence of 38 J/cm 2 for a number of pulses that varied depending on the size of the treatment area. The change in erythema was determined by using standard image-editing software to compare CIE L*a*b* values in pre- and postprocedure digital images. We specifically used the Δa* value to assess erythema by calculating the difference in a* between average values for rosacea-involved areas and average values for adjacent skin in uninvolved sites before and after treatment. Results: Upon follow-up, there was a statistically significant reduction in erythema in all patients after the first or second treatment. All patients reported only minor discomfort during the procedure, and no subsequent adverse effects were seen. Conclusion: The high degree of efficacy and the relative absence of discomfort in treatment compared with other light-based therapies make ALA-PDT an attractive alternative. We believe this modality is an efficacious adjunct to standard first-line therapies and should be considered a possible alternative first-line therapy.